Immunocorrelates of CAF family adjuvants. (October 2018) - Pedersen, Gabriel Kristian; Andersen, Peter; Christensen, Dennis
Abstract: The development of the CAF family adjuvant was initiated around 20 years ago when Statens Serum Institut was preparing its first generation protein based recombinant subunit vaccine against tuberculosis for clinical testing, but realized that there were no clinically relevant adjuvants available that would support the strong CMI response needed. Since then the aim for the adjuvant research at Statens Serum Institut has been to provide adjuvants with distinct immunogenicity profiles correlating with protection for any given infectious disease. Two of the adjuvants CAF01 and CAF09 are currently being evaluated in human clinical trials. The purpose of this review is to give an overview of the immunocorrelates of those CAF adjuvants furthest in development. We further aim at giving an overview of the mechanism of action of the CAF adjuvants.